The diagnosis and management of metastatic bone disease in general practice. Issue 7 (July 2021) - Cheyne, Natalie; Nichols, David; Kumar, Amit
As cancer treatment improves and survival rates continue to increase, clinicians are seeing increasing numbers of patients with metastatic bone disease (MBD). This term describes cancer that has originated in another organ and subsequently spread to the bone. It is a condition that can severely impact the quality of life for an individual and the treatment is often not curative. This article aims to cover the management of MBD, from early recognition to secondary care interventions. The care of individuals with MBD is evolving in the UK, with the development of specialist regional referral pathways to facilitate prompt and timely management.